Mole Drainage to Enhance Soybean Production in Waterlogged Vertisols - Rao, K.V Ramana; Kishore, Ravi; Singh, Ramadhar (Journal of Agricultural Engineering, 2009)
Vertisols have poor internal drainability when wet, requiring closely spaced drains for excess water removal. Mole drainage is a pipe-less drainage technology popular in UK, New Zealand and Australia. Its use in fine textured soils using standard mole ploughs is mainly confined to those countries where mole plough development took place. In India, few laboratory studies were reported apart from one field study at Digod, Rajasthan on mole drainage. A 4-year (2004–2007) field experiment was carried out at the Central Institute of Agricultural Engineering, Bhopal on the feasibility of mole drainage for draining excess rain water in vertisols. A 56 PS wheeled tractor was used in drawing mole drains at 2, 4 and 6 m spacings and at a constant depth of 0.60 m at a grade of 0.8 per cent. In each of the spacing, 4 lateral drains were drawn to a length of 60 m. The soil moisture content was 22.5% at moling depth. The crop yields increased by about 50% in the mole drained plots, as compared to the control. The cost of installation of mole drains was recovered in the first year of installation. For four years, the drains were functioning well as a result of which soybean yields increased in mole drained area.